Presence of 6PPD-quinone in runoff water samples from Norway using a new LC–MS/MS method - Kryuchkov, Fedor; Foldvik, Anders; Sandodden, Roar; Uhlig, Silvio (Frontiers in Environmental Chemistry, 2023)
The chemical 6PPD-quinone is highly toxic to some fish species of the Oncorhynchus and Salvelinus genera and is the oxidation product of the common car tire additive 6PPD. We present a new sample preparation method that involves liquid-liquid extraction of water samples followed by silica-based solid phase extraction prior to LC–MS/MS analysis. The new sample preparation method showed good analyte recovery from spiked water samples (78–91%) and a low ion suppression effect, surpassing previously published methods. This new method was successfully validated, achieving a limit of quantification of 5 ng/L and estimated expanded measurement uncertainty of 18.6%. In a proof-of-concept study, the method was applied to several water samples from various sources in southern Norway. These were runoff samples from tunnel washing, from a tunnel runoff treatment plant and downstream of the plant drain. In addition, two water samples from puddles were included: one was run-off from an artificial soccer turf field and one from a puddle on a country road. The results of the analyses revealed that the concentration of 6PPD-quinone was above the LC50 reported for coho salmon (Oncorhynchus kisutch) in all samples except the samples from and downstream of the treatment plant. The highest measured concentration was 258 ng/L, which is the 2.7-fold of the reported LC50 in coho salmon (95 ng/L). Our initial data emphasize the need for more comprehensive environmental monitoring of 6PPD-quinone as well as toxicological studies in aquatic organisms.